Norman Angell and the logic of economic interdependence revisited: 1914, 2014 - Tan, Er-Win; Kim, Seung Jin; Kim, Gi-Seung (Springer Verlag (Germany), 2015)
There are regional fears that Beijing will use its growing clout to embark on an aggressive, expansionist policy in International Relations, hence the possibility of a collision course with the USA reminiscent of how Anglo-German tensions at the beginning of the twentieth century escalated into World War One. Closer scrutiny, however, suggests grounds for downplaying the likelihood of such a scenario. We outline this argument based on the following points: (i) there is a much higher level of economic interdependence between China and the USA today, compared to Britain and Germany, (ii) the corresponding levels of nationalism in China and the USA are lower than in Britain and Germany, (iii) the political alignments of international relations in the Asia Pacific in 2014 are less ambiguous than those in Europe in 1914, hence less potential for diplomatic miscalculation and (iv) the military and economic instruments of power that the USA and China possess, by being far more lethal than those held by Britain and Germany in 1914, would render any conflict between them an unacceptably costly catastrophe.